2021
DOI: 10.3390/ijms22116053
|View full text |Cite
|
Sign up to set email alerts
|

Highly-Efficient Sulfonated UiO-66(Zr) Optical Fiber for Rapid Detection of Trace Levels of Pb2+

Abstract: Lead detection for biological environments, aqueous resources, and medicinal compounds, rely mainly on either utilizing bulky lab equipment such as ICP-OES or ready-made sensors, which are based on colorimetry with some limitations including selectivity and low interference. Remote, rapid and efficient detection of heavy metals in aqueous solutions at ppm and sub-ppm levels have faced significant challenges that requires novel compounds with such ability. Here, a UiO-66(Zr) metal-organic framework (MOF) functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Briefly, the MOF precursor mixture was heated at 120 °C for 3 d and then extensively washed in DMF and methanol and then evacuated under reduced pressure (see Experimental in Supporting Information). This UiO-66-SO 3 H work demonstrates permanent microporosity with pores of 6.3 and 9.5 Å, and a similar Brunauer–Emmett–Teller (BET) surface area of 392 m 2 /g compared to previous reports of 491 m 2 /g, collapsing upon activation, or 550 m 2 /g. The UiO-66-SO 3 H gave a particle size distribution of 312 ± 69 nm, compared to the UiO-66 distribution of 296 ± 40 nm as measured by an SEM survey image. After characterization showed that the MOF retained desirable factors of crystallinity, SO 3 H groups, and pore sizes under 1 nm (Figures S3 and S4, Supporting Information), the activated MOF was added to a CTA/DCM solution, stirred, sonicated, and solution cast into a glass dish.…”
Section: Resultssupporting
confidence: 64%
“…Briefly, the MOF precursor mixture was heated at 120 °C for 3 d and then extensively washed in DMF and methanol and then evacuated under reduced pressure (see Experimental in Supporting Information). This UiO-66-SO 3 H work demonstrates permanent microporosity with pores of 6.3 and 9.5 Å, and a similar Brunauer–Emmett–Teller (BET) surface area of 392 m 2 /g compared to previous reports of 491 m 2 /g, collapsing upon activation, or 550 m 2 /g. The UiO-66-SO 3 H gave a particle size distribution of 312 ± 69 nm, compared to the UiO-66 distribution of 296 ± 40 nm as measured by an SEM survey image. After characterization showed that the MOF retained desirable factors of crystallinity, SO 3 H groups, and pore sizes under 1 nm (Figures S3 and S4, Supporting Information), the activated MOF was added to a CTA/DCM solution, stirred, sonicated, and solution cast into a glass dish.…”
Section: Resultssupporting
confidence: 64%
“…At the same time, when the content of Pb 2+ ions is at quite a low level, a perfect linear relationship between fluorescence quenching efficiency and concentration was illustrated. When compared with other MOFs, the Zn-TCPP-MOF detected Pb 2+ ions in water, at very low concentrations, as well as at its fully lower limit of detection (LOD) of 4.99 × 10 − 8 M. The SO 3 H-UiO-66(Zr) MOF system, functionalized with an SO 3 H group and usually installed in the end-face of an optical fiber, implemented the function of detecting Pb 2+ in water at 25.2, 43.5, and 64.0 ppm levels [ 74 ]. The proposed removal mechanism is based on the adsorption of [Pb(OH 2 ) 6 ] 2+ in water on SO 3 H-UiO66(Zr) because of a strong affinity between functionalized MOF and lead, as shown in Figure 9 .…”
Section: Lmofs For Hazardous Materials Detectingmentioning
confidence: 99%
“…The sensor exhibited a Pb 2þ sensitivity of 1.2 nm∕μg∕L, and the lower limit of detection was 0.001 ppm. Nazari et al 82 developed an efficient sulfonated UiO-66(Zr) optical fiber for the rapid Pb 2þ detection. UiO-66(Zr) metal-organic frameworks (MOFs) functionalized with SO 3 H groups ½SO 3 H-UiO-66ðZrÞ was modified on the end face of the optical fiber to detect lead cations in water at 25.2, 43.5, and 64.0 ppm levels.…”
Section: Leadmentioning
confidence: 99%
“…The sensor exhibited a Pb2+ sensitivity of 1.2 nm/μg/L, and the lower limit of detection was 0.001 ppm. Nazari et al 82 . developed an efficient sulfonated UiO-66(Zr) optical fiber for the rapid Pb2+ detection.…”
Section: Water Quality Monitoringmentioning
confidence: 99%